Private capital flows to developing countries : the road to financial integration - World Bank. (New York : Oxford University Press for the World Bank, 1997)
The report analyzes the causes and effects of integration, with a particular emphasis on how developing countries in the nascent stages of integration can learn from the experiences of the more rapidly integrating developing countries. The first half of the report provides the setting, analyzing the process of financial integration, the forces driving private capital to developing countries, and the potential benefits of integration. The second half looks at the domestic policy challenges that developing countries must overcome, including the macroeconomic problems of an overheating economy, reforms in the domestic financial sector, and the agenda for capital market reform.
Errata slip inserted.
Includes bibliographical references (p. 391-406).
rpm 20/09/16
Loans
Keywords: Investments, Foreign; Capital movements